Pengaruh Minat, Opini dan Aktivitas Konsumen Terhadap Keputusan Pembelian di Shabu Auce Resto Semarang - Fahrina Zahra; Saryadi Saryadi (Universitas Diponegoro, 2017)
This research is motivated by the decreasing number of visitors in 2014 until 2016. The objective of this study was to determine the effect of lifestyle aspect, consist of interests, opinions, and activities on consumers purchase decision at Shabu Auce Restaurant Semarang. This study was an explanatory research using questionnaire to collect data. Purposive sampling technique were used to get samples. A total of 100 respondents who visited Shabu Auce Restaurant Semarang were collected. This study used quantitative analysis technique using validity test, reliability test, coefficient of correlation, simple and multiple regression analysis, coefficient of determination, significance test (T test), and the F test ( multiple regression). The result of simple regression test showed that all of the lifestyle aspect, consists of interests, opinions, and activities, had a positive significant influence toward the purchase decision. Increasing perception of interests, opinions, and activities will increase consumers purchase decision as well. The result of F test in multiple linear regression showed that interests, opinions, and activities simultaneously influence the purchase decision. The most dominant variable was activities which had the largest standardized regression coefficient.